Neuroketotherapeutics: A modern review of a century-old therapy. (July 2018) - Koppel, Scott J.; Swerdlow, Russell H.
Abstract: Neuroketotherapeutics represent a class of bioenergetic medicine therapies that feature the induction of ketosis. These therapies include medium-chain triglyceride supplements, ketone esters, fasting, strenuous exercise, the modified Atkins diet, and the classic ketogenic diet. Extended experience reveals persons with epilepsy, especially pediatric epilepsy, benefit from ketogenic diets although the mechanisms that underlie its effects remain unclear. Data indicate ketotherapeutics enhance mitochondrial respiration, promote neuronal long-term potentiation, increase BDNF expression, increase GPR signaling, attenuate oxidative stress, reduce inflammation, and alter protein post-translational modifications via lysine acetylation and β-hydroxybutyrylation. These properties have further downstream implications involving Akt, PLCγ, CREB, Sirtuin, and mTORC pathways. Further studies of neuroketotherapeutics will enhance our understanding of ketone body molecular biology, and reveal novel central nervous system therapeutic applications. Highlights: Several approaches exist for achieving ketosis. Ketosis approaches produce pervasive molecular effects. These approaches may potentially benefit multiple neurologic conditions.